2007
DOI: 10.1161/hypertensionaha.107.087262
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of All-Cause Mortality in Clinical Ambulatory Monitoring

Abstract: Abstract-The prognostic value of sleep blood pressure reported by recent studies is variable. Our aim was to examine the relationship of sleep blood pressure, measured by 24-hour ambulatory blood pressure monitoring, with all-cause mortality. We studied a cohort of 3957 patients aged 55Ϯ16 (58% treated) referred for ambulatory monitoring (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) Key Words: ambulatory blood pressure monitoring Ⅲ dipping Ⅲ mortality Ⅲ cohort Ⅲ sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
233
4
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(265 citation statements)
references
References 45 publications
17
233
4
11
Order By: Relevance
“…Thus, this study suggests that home blood pressure measurement may be a suitable alternative if a correct blood pressure target is chosen, but more studies are needed before home blood pressure can be recommended for antihypertensive treatment titration. Finally, it has to be emphasized that in contrast to home blood pressure measurement, 24-h blood pressure measurement can give additional important information about night-time blood pressure, 9 dipping status [26][27][28] or 24-h blood pressure variability, 13 all of which may lead to improved risk stratification of individuals with hypertension. On the other hand, potential drawbacks of 24-h blood pressure measurement include additional costs and patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study suggests that home blood pressure measurement may be a suitable alternative if a correct blood pressure target is chosen, but more studies are needed before home blood pressure can be recommended for antihypertensive treatment titration. Finally, it has to be emphasized that in contrast to home blood pressure measurement, 24-h blood pressure measurement can give additional important information about night-time blood pressure, 9 dipping status [26][27][28] or 24-h blood pressure variability, 13 all of which may lead to improved risk stratification of individuals with hypertension. On the other hand, potential drawbacks of 24-h blood pressure measurement include additional costs and patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, increasing evidence suggests that nocturnal BP is the more sensitive predictor of CVD outcomes than either daytime or 24-hour BP, and thus nocturnal BP measurement is becoming an important part of clinical practice. [1][2][3][4][17][18][19][20] NOCTURNAL BP AND CARDIOVASCULAR RISK A recent systematic review of 23 856 hypertensive patients and 9641 subjects from population cohorts from Asia, Europe and South America by Hansen et al 20 revealed that nocturnal BP is a significant risk factor for mortality and cardiovascular morbidity in both hypertensive patients and the general population, even when adjustments were made for daytime BP. The hazard ratios associated with each 10-mm Hg increase in nocturnal systolic BP were 1.16 or 1.14 for total mortality and 1.19 or 1.15 for cardiovascular morbidity in hypertensive patients or the general population, respectively (both Po0.001).…”
Section: How To Evaluate Nocturnal Bpmentioning
confidence: 99%
“…For example, an untreated man whose daytime BP 30 In contrast, other reports have concluded that a patient with this profile would be at increased mortality risk, regardless of the patient's 24-hour BP levels. [17][18][19][20]30 The clinical implications of nondipping in the absence of nocturnal hypertension may vary with age, smoking status, presence of antihypertensive drugs and co-morbidities such as diabetes, chronic kidney disease and preexisting CVD. Nevertheless, the association of nondipping with excess mortality rather than cardiovascular morbidity [17][18][19][20][21] raises the possibility that nondipping is a marker of pre-existing or concurrent diseases ( Figure 2).…”
Section: Nocturnal Bp Dipping and Cardiovascular Riskmentioning
confidence: 99%
“…38 In another prospective study that recruited 3957 patients, a superior prognostic significance for all-cause mortality was attributed to nocturnal hypertension in comparison with the nondipping status defined according to either systolic BP or diastolic BP fall. 6 A meta-analysis of 3468 hypertensive patients' nighttime ambulatory BP significantly predicted allcause CV and non-CV mortality, coronary heart disease and stroke, independently of confounders. In addition, nighttime ambulatory BP adds to the prognostic significance of daytime ambulatory BP for all of the end points.…”
Section: Vascular and Cerebral Adaptationsmentioning
confidence: 99%
“…2 Along with 24-h systolic and diastolic BP, both reflecting the cardinal clinical components of the haemodynamic load magnitude, the prognostic impact of diverse time-dependent ABPM components (namely daytime and nighttime BP) and circadian BP variability patterns (such as dipping status, nightto-day BP ratio, early morning surge) have been previously investigated. 3 Although both averaged nocturnal BP values [4][5][6] and blunted nocturnal decrease with respect to daytime BP [7][8][9] were found to be associated with subclinical target organ damage and to heighten CV morbidity and mortality, their relative importance is still controversial.…”
Section: Introductionmentioning
confidence: 99%